2018
DOI: 10.1186/s12984-018-0425-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gait support in patients with spinocerebellar degeneration by a wearable robot based on synchronization control

Abstract: BackgroundSpinocerebellar degeneration (SCD) mainly manifests a cerebellar ataxic gait, leading to marked postural sway and the risk of falling down. Gait support using a wearable robot is expected to be an effective solution to maintaining the status quo and/or delaying symptom progression. The aim of this study was to evaluate the effects of gait support in patients with SCD by using a wearable robotic system called curara ®; while undergoing walking tests.MethodsThe curara system assists both the hip and kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…With this gait assist system, patients could walk more smoothly with an increased harmonic ratio while wearing the exoskeleton compared to the gait without the exoskeleton. There were no major changes in gait speed, stride length, and cadence in most patients [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…With this gait assist system, patients could walk more smoothly with an increased harmonic ratio while wearing the exoskeleton compared to the gait without the exoskeleton. There were no major changes in gait speed, stride length, and cadence in most patients [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Exoskeletons included in the literature review. From left to right and top to bottom: A diagram showing the locations of the active joints of the exoskeletons included in the literature review, HAL (Image courtesy of Cyberdine, Inc.), WPAL (Reproduced from [ 39 ]), H2 (Reproduced from [ 40 ]), REX (Reproduced from [ 41 ]), Ekso (Image courtesy of Paolo Milia, Prosperius Institute, Neurorehabilitation and Robotic Area, University of Perugia, Umbertide, Italy), ReWalk (Image courtesy of ReWalk Robotics), Robin (Image courtesy of Hyunsub Park, Applied Robot Technology R&D Group, Korea Institute of Industrial Technology, Korea), CUHK-EXO (Reproduced from [ 42 ]), ITRI (Reproduced from [ 43 ]), Vanderbilt Exoskeleton (Image courtesy of Michael Goldfarb, Vanderbilt University, Nashville), Indego (Reproduced from [ 44 ]), ARKE (Image courtesy of Edward Lemaire, Ottawa Hospital Research Institute, Centre for Rehabilitation Research and Development, Ottawa, Canada), Curara (Reproduced from [ 45 ]), Arazpour2103a (Image courtesy of Mokhtar Arazpour, Department of orthotics and prosthetics, University of Social Welfare and Rehabilitation Sciences, Tehran, Islamic Republic of Iran), Kim2013 (Image courtesy of Kim Gyoosuk, Korea Workers Compensat & Welf Serv, Rehabil Engn Res Inst, Incheon, South Korea), Chang2017 (Reproduced from [ 46 ]), SMA (Reproduced from [ 47 ]), Keoogo (Reproduced from [ 48 ]), Kinesis (Image courtesy of Antonio J. del Ama, Electronic Technology Deparment, Rey Juan Carlos University, Spain), Lerner2017 (Image courtesy of Thomas Bulea, Rehabilitation Medicine Department, National Institutes of Health Clinical Center, Bethesda, USA), Alter G Bionic Leg (Image courtesy of Luna Solution, S.L. ), Arazpour2013b (Image courtesy of Monireh A. Bani, Department of Orthotics and Prosthetics, University of Social Welfare and Rehabilitation Sciences, Tehran, Islamic Republic of Iran), Kawasaki2017 (Image courtesy of Ohata Koji, Department of Human Health Sciences, Kyoto University Graduate School of Medicine, Japan), Yeung2017 (Reproduced from [ 49 ]), and Boes2017 (Reproduced from [ 50 ]).…”
Section: Reviewmentioning
confidence: 99%
“…The basic mechanisms of curara® are characterized by a torque-sensing technique and synchronized-based control system. Detailed information regarding curara® is shown in our previous reports [13,14]. Curara® is considered as a pseudo-passive device [12] that consists of a streamlined structural design of small actuators and a small rechargeable battery.…”
Section: Methods Participants and Instrumentationmentioning
confidence: 99%
“…Furthermore, to apply this robot to people with stroke or cerebellar ataxia, we identi ed the assist conditions and evaluated its immediate effect on gait [13,14]. We found that several gait parameters were improved temporarily in people with stroke or cerebellar ataxia while wearing curara® with certain assist conditions [13,14]. The remaining issue to be resolved is whether curara® can improve gait through rehabilitation for a speci ed period.…”
Section: Introductionmentioning
confidence: 99%